Dexamethasone added to Bupivacaine prolongs the duration of analgesia for supraclavicular brachial plexus block (Bangladesh Journal of Medical Science, 2018)
Background: Local anaesthetics alone for supraclavicular brachial plexus block provide good operative conditions but have shorter duration of postoperative analgesia. Numerous adjuncts have been added to enhance the efficacy of the block. Steroids have anti-inflammatory as well as analgesic effects.Objectives: This study has been undertaken with a view to find out the efficacy of dexamethasone to increase the duration of analgesia when used as an adjuvant to bupivacaine in supraclavicular brachial plexus block in upper extremity surgery.Methods: Total 60 patients of ASA I and II undergoing upper extremity surgery under brachial plexus block were randomly divided into two equal groups of 30 each; Bupivacaine group-‘’A’’ received 0.5% bupivacaine 2 mg/kg with distilled water 15 ml and Dexamethasone group-‘’B’’ received 0.5% bupivacaine 2 mg/kg with dexamethasone (0.2mg/kg) with distilled water 15 ml. The duration of analgesia in the two groups were compared.Results: There was markedly prolonged duration of analgesia in dexamethasone group. The mean duration of analgesia in bupivacaine group was 455 ± 17.09 minutes, whereas in dexamethasone group it was 864.50 ± 25.19 minutes. The results were statistically highly significant.Conclusion: Dexamethasone when added to bupivacaine in brachial plexus block it results significantly prolonged duration of post-operative analgesia, which was significantly higher in comparison to bupivacaine when it is used alone.Bangladesh Journal of Medical Science Vol.17(2) 2018 p.296-301